Analysis of the coupling of twenty-five benzothiazole analogs with the β1-adrenergic receptor using a theoretical model - Alvarez-Ramirez, Magdalena; Rosas-Nexticapa, Marcela; Mateu-Armad, Maria Virginia; Bonilla- Zavaleta, Enrique (Brazilian Journal of Science, 2025)
Some benzothiazoles have been developed with biological activity on the cardiovascular system through interaction with different biomolecules; however, the coupling with the β1-adrenergic receptor is not clear. This research aimed to determine the interaction of some benzothiazole analogs (1-25) with the β1-adrenergic receptor using some theoretical models. In this way, 2ycv protein and the controls (metoprolol, propranolol, and cyanopindolol) were used as theoretical tools in the DockingServer software. The results showed differences in the interaction of benzothiazole derivatives compared with the controls. Other data indicate that the inhibition constant (Ki) for benzothiazole analogs 10, 22, 23, and 25 was lower compared with metoprolol and cyanopindolol. All these data indicate that compounds 10, 22, 23, and 25 may act as β1-adrenergic receptor inhibitors, translated into changes in blood pressure. Therefore, the benzothiazole derivatives 10, 22, 23, and 25 could be good antihypertensive agents.